Gambaran Pengetahuan Dan Sikap Ibu Hamil Tentang Tanda Bahaya Selama Kehamilan Di Klinik Romauli - Lilis Sumardiani (STIKes Santa Elisabeth Medan, 2020)
The risk of maternal death is higher due to the delay factor, which is an indirect cause of maternal mortality. There are three risks of delay, namely being late in making decisions to be referred to (including being late in recognizing danger signs during pregnancy), being late to the health facilities during an emergency and being late in getting adequate services by health workers. The main causes of maternal deaths in Indonesia are bleeding (28%), eclampsia (24%), and infection (11%). The cause of maternal death can be prevented by adequate prenatal care. This study aims to describe the knowledge of attitudes of pregnant women about danger signs during pregnancy at Romauli ClinicMethod. This type of research is descriptive analytic with cross sectional approach. The total populations are all pregnant women who did the examination at Romauli Clinic from April to May are 120 pregnant women. The number of samples taken is a portion of the population, namely 25 pregnant women who are determined accidentally. The measuring instruments used are questionnaires and questionnaires. Data analysis uses 2x2 chi square test.Result. The results of this study indicate that there is an overview between knowledge and attitudes of pregnant women about danger signs duringElisabteh Health Journal : Jurnal Kesehatan, Vol. V No. 01 (Juni, 2020) : V-01 E-ISSN 2541-4992pregnancy by observing the results of statistical tests obtainead p = 0.003 <α 0.05. Because the significance value is smaller than the real level of 0.05,Duscussion. it can be concluded that there is an overview between the knowledge of the attitudes of pregnant women about danger signs during pregnancy at Romauli Clinic Marelan District Medan City.